2021
DOI: 10.3390/md19100532
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Vaccinia Virus Harboring Aphrocallistes vastus Lectin Inhibits the Growth of Cervical Cancer Cells Hela S3

Abstract: Aphrocallistes vastus lectin (AVL) is a C-type marine lectin produced by sponges. Our previous study demonstrated that genes encoding AVL enhanced the cytotoxic effect of oncolytic vaccinia virus (oncoVV) in a variety of cancer cells. In this study, the inhibitory effect of oncoVV-AVL on Hela S3 cervical cancer cells, a cell line with spheroidizing ability, was explored. The results showed that oncoVV-AVL could inhibit Hela S3 cells growth both in vivo and in vitro. Further investigation revealed that AVL incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In contrast, Raf-1, with cross-talk between these pathways, impedes viral replication. Previous studies illustrated Sorafenib, which is an inhibitor targeting Raf kinases (Raf-1/C-Raf, wide-type B-Raf, and mutant B-Raf) [52], promoted oncoVV-AVL replication in Hela S3 cell lines [24]. Our current data illustrated that oncoVV-AVL replication was significantly downregulated in the presence of the inhibitors of PI3K/Akt, MAPK/ERK, and Hippo/MST pathways.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In contrast, Raf-1, with cross-talk between these pathways, impedes viral replication. Previous studies illustrated Sorafenib, which is an inhibitor targeting Raf kinases (Raf-1/C-Raf, wide-type B-Raf, and mutant B-Raf) [52], promoted oncoVV-AVL replication in Hela S3 cell lines [24]. Our current data illustrated that oncoVV-AVL replication was significantly downregulated in the presence of the inhibitors of PI3K/Akt, MAPK/ERK, and Hippo/MST pathways.…”
Section: Discussionsupporting
confidence: 66%
“…We have previously demonstrated that oncolytic vaccinia virus harboring Aphrocallistes vastus lectin (oncoVV-AVL) had substantial antitumor effects on colorectal cancer, hepatocellular carcinoma, and cervical cancer [23,24]. However, the mechanism of oncolysis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Rodríguez et al reported that ERK activators increased viral yields, whereas ERK silencing decreased viral multiplication [ 38 ]. Our previous study found that oncoVV-AVL interfered with the Raf/ERK pathway in Hela S3 cells [ 22 ]. In Figure 5 a,d, although both Sorafenib (Raf inhibitor) and U0126 (MEK inhibitor) decreased oncoVV replication, the expression levels of both ERK and phosphorylated ERK (p-ERK) were not upregulated by oncoVV as compared with PBS, indicating that oncoVV replication in Hep-3B cells was independent of this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The oncolytic vaccinia virus (oncoVV) used in this research is a Western Reserve (WR) strain engineered for viral thymidine kinase (TK) gene deletion [ 19 ]. Our previous studies have shown that oncoVV armed with Tachypleus tridentatus lectin (oncoVV-TTL) [ 20 ], Aphrocallistes vastus lectin (oncoVV-AVL) [ 21 , 22 , 23 , 24 ], white-spotted charr lectin (oncoVV-WCL) [ 25 ], and Asterina pectinifera lectin (oncoVV-APL) elicited cytotoxicity to a variety of cancer cells by enhancing viral replication through the suppression of the antiviral response of cells and inducing cell apoptosis. In this study, the cytotoxic effects of four vaccinia virus variants constructed from marine lectins were compared, and the mechanisms of action of these viruses were further investigated in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding sponge ( Aphrocallistes vastus ) C-type lectin enhanced the cytotoxic action of oncolytic vaccinia virus (oncoVV) toward tumor cells. The complex formed between the lectin and the virus exerted an in vitro as well as an in vivo growth inhibitory action on Hela S3 cervical cancer cells [ 227 ].…”
Section: Other Biological Activities Of Lectinsmentioning
confidence: 99%